Social Environment in Supporting Gifted Students’ Academic Achievement - Dianti Endang Kusumawardhani (Jurnal Psikologi Sosial, 2018)
The implementation of acceleration program for the gifted students was problematic and has been dismissed by Indonesian Government in 2014. 240 first year students from three high schools in Jakarta participated in this study. The study focused on the social environment that is projected in accelerated and regular classrooms. Type of Classrooms is associated with Accelerated learning. Path analysis model was used to develop the relationships between latent and manifest variables. This study employed PLSPATH program to analyse the data. The results showed accelerated learning is positively related to Self-Regulated Learning in Biology but there is only a very weak relation in Mathematics. Accelerated learning positively and marginally related to Self-Efficacy in Biology, but negatively and marginally related to Mathematics Self-Efficacy. There is a significant relationship between Accelerated learning and Achievement in both Mathematics and Biology.